Production of nanochitin by combination of biochemical and physical methods: potential use for salt reduction in food products - Nguyen, Thi Cha; Ho, Ha Phu; Nguyen, Tien Thanh (Vietnam Journal of Science and Technology, 2025)
Nanochitin is a product of the chitin size-reduction process. Compared to chitin, nanochitin possesses several new properties, thereby increasing its potential applications. This study presents the production of nanochitin from Vietnamese white leg shrimp chitin by combining biochemical and physical methods. In this process, chitin was first hydrolyzed using a chemical catalyst (acid) and a biological catalyst (enzyme), then further size-reduced through physical treatment using ultrasonic waves. In the experiment, chitin was incubated with enzyme (at 4 g/kg material ratio) at 50°C for 30 minutes and then hydrolyzed with 3N HCl at an acid/chitin ratio of 25:1, at 80°C for 180 minutes. The hydrolysate was subsequently subjected to ultrasound treatment at 75% amplitude for 33 minutes with a solvent/substrate ratio of 76:1 mL/g. The final product was obtained by freeze-drying. The resulting nanochitin had an average size of 228 nm, high solubility of 78.4%, and a zeta potential of 29 mV. At a concentration of 80 μg/mL, nanochitin enhanced the saltiness of a 0.65% NaCl solution, making it comparable in perceived saltiness to a 0.69% NaCl solution. This saltiness-enhancing effect was applied to the seasoning powder of instant noodles. Supplementing nanochitin at 1.16% of the salt weight allowed a 5.8% reduction in NaCl content in the seasoning packet while maintaining equivalent saltiness to the original formulation. These results suggest that nanochitin can be used as a saltiness-enhancing additive in food products, offering a promising approach for dietary salt reduction in response to current overconsumption trends.